The Effect of Liquidity, Non-Performing Financing, and Return on Asset on The Distribution of Islamic Banking Financing in Indonesia - Marwah Dwi Cahyani; Ismawati; Muh Rasul Kahar (www.amertainstitute.com, 2023)
This research aims to determine the effect of liquidity, Non-Performing Financing, and Return On Asset on the distribution of Islamic banking financing in the period from 2011 to 2020. The study is a quantitative research that employs multiple linear regression tests as a hypothesis test and classical assumption tests before conducting hypothesis testing. The data used in this study were secondary data obtained from annual report of each bank published from 2011 to 2021. The population in this study consists of Islamic commercial banks in Indonesia, which originally consisted of 15 banks. However, this year, three banks, namely BRI Syariah, BNI Syariah, and Syariah Mandiri, have merged to become Bank Syariah Indonesia. The sampling technique used in this study was purposive sampling, proposing several criteria to ensure that the sample was representative of the population. Therefore, five Islamic commercial banks were selected as the sample size. The results indicate that liquidity and Non-Performing Financing have no effect on the distribution of Islamic banking financing in Indonesia, while Return On Asset has a significant effect on the distribution of Islamic banking financing in Indonesia. Furthermore, liquidity, Non- Performing Financing, and Return On Asset have a joint effect on the distribution of Islamic banking financing in Indonesia.